Legal and Ethical Laws Governing Human Medical Research and Experimentation - Okafor, Amalachukwu S. (2017)
Human Medical research and experimentation is important to the development of life science and helpful to the health of human beings. Ethics is an essential dimension of human research as it can be considered as both a discipline and practice. The need for human medical research cannot be over emphasized; it ensures a progression in the curative as well as scientific aspect of medicine which is beneficial to all mankind. In view of desire of humans to live and not die notwithstanding new diseases emerging, scientific research must be encouraged to remain on top of all forms of health challenges. The purpose of this work is to further the arguments on the relevance of human medical research and experimentation as well as the necessity to ensure that adequate regulations are put in place to checkmate the excesses of researchers particularly when conducting experiments with developing countries like Nigeria, such that requisite ethical values are sustained. It reviews widely accepted ethical principles that govern the conduct of research with human participants. Application of research ethics committees to monitor and approve prior review of proposed research that involves human participants in research has been elucidated along with the legal and practical implications. There are so many challenges brought about by human experimentation, which should be paid more attention to by law in order to protect the right of the subject. International as well as domestic laws are enacted in order to beat the illegitimate human experiment, while criminal countermeasures should be taken to redeem the failure of medical researchers in adhering to these ethical issues which are internationally recognized. Legal measures are recommended to emphasize the need to protect right to life notwithstanding the burning urge to enhance science and medicine, in Nigeria and globally